Unpacking Bias, Building Equality: Gender Equality Practices in PAI and Rohis Learning - Camelia Carmilita; Ashwini; Audyla Nurfala; Anissa Rahma Sari; Suci Amelia (WISE Pendidikan Indonesia, 2026)
This study examines the implementation of gender equality in the teaching of Islamic Religious Education (PAI) and extracurricular activities of Rohis at SMAN 15 Bandar Lampung. Using a descriptive qualitative approach, the study explores how gender equality principles are applied in the curriculum, teaching methods, classroom interactions, and student participation. Data were collected through interviews, observations, and documentation to gain a comprehensive understanding of the application of gender equality in both formal and non-formal learning contexts. The findings show that gender equality is effectively applied in PAI teaching through the selection of inclusive content and equal participation opportunities for male and female students. Furthermore, structured group discussions and the teacher's pedagogical control ensure equal opportunities for leadership and cross-gender involvement. The integration of gender equality in Rohis activities further reinforces these values outside the classroom, providing equal opportunities for students to develop and achieve success. This study emphasizes the importance of active teacher involvement in moderating classroom interactions and ensuring that gender equality is not just a normative concept, but a lived experience for students. The study also suggests that schools can strengthen gender equality by ensuring consistency in practices across the classroom, extracurricular activities, and institutional culture.